Presentation of the special issue : the collective body of laughter - Gusmão, Rita; Azevedo, Mariana; Cordeiro, Marcelo (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
Presentation of the special issue "The collective body of laughter".